Teacher Skills Improvement Training in Writing PTK-Based Articles - Rasidin, Rasidin; Thontawi, M Thontawi; Hindun, Hindun; Nasir, Nasir; Jamila, Jamila; Netti Zurnelli; Fransisca, Susi; Yahuda, M.Yahuda (Jurnal Pengabdian kepada Masyarakat Nusantara, 2026)
Community service activities were carried out by the Islamic Religious Education Study Program team of UIN Sultan Thaha Saifuddin Jambi at IAI Al-Mujaddid Sabak Tanjung Jabung Timur with the aim of creating a productive and innovative academic environment, as well as encouraging teachers to continue to contribute to improving the quality of education. This activity is expected to be a positive initial step in encouraging a culture of research and writing among teachers. This training was attended by 30 students and 15 lecturers from various educational backgrounds. In this activity, an explanation and understanding of the orientation and assistance in writing articles based on PTK was provided, providing practical guidance and effective strategies to produce quality written works and contribute to the development of education. In addition, this activity is also a forum for expressing creative ideas conceptually and practically. This training does not only focus on writing theory, but also involves a practical session where participants are given the opportunity to draft their own articles. Participants are guided directly by Sahade and the facilitator team. Therefore, this training aims to increase awareness, knowledge, and skills in optimizing PTK-based writing skills. The results of this training show that participants are very enthusiastic and actively participate, even though there are challenges related to compiling and analyzing writing. This training activity is expected to improve writing skills among students, lecturers and teachers and can continue to develop, along with technological advances in this modern era, and be a positive first step in encouraging a culture of research and writing.